SPIRITUALITY AMONG THE PROFESSORIATE AT A PRIVATE UNIVERSITY IN LIMA, PERU - Gootjes Kasel, Dirk (2016)
This study examined the professoriate view of spirituality at a private university in Lima, Peru. A two-phase, sequential mixed method was used. Two hundred forty professors completed Paloutzian and Ellison’s (1982) Spiritual Well-Being Scale (SWBS) for the quantitative phase. Five research questions exploring the professors’ gender, general area of teaching (humanities vs. sciences), highest university degree earned, age, and total years of university teaching experience were analyzed to determine if any significant differences existed within those variables. Two non-parametric tests were used: the Mann-Whitney U test and the Kruskal-Wallis Test. It was discovered only gender showed a significant difference. Five surveyed professors participated in the focus group phase exploring significant gender difference on the spiritual well-being scores. Five questions explored this difference between males and females. Four themes emerged: gender role enculturation, biological motherhood, stress, and internal strength.